POLA KOMUNIKASI ORGANISASI: KOMUNIKASI VERTIKAL PADA CV. KIOS CETAK UTAMA SURABAYA - Didik Sugeng Widiarto (Metacommunication, 2018)
ABSTRACT                 Communication that occurs following the path from top to bottom or from bottom to top as it is called vertical communication. understanding that there is communication that occurs from superiors to subordinates or from subordinates to superiors. The content of communications from superiors to subordinates often in the form of a message containing the duties and responsibilities that must be carried out by subordinates. as well as on the rules that apply in running the organization in an institution, the rules that must be obeyed and executed. Upward communication is a message about the work done by subordinates, both directly and indirectly. as well as about the dissatisfaction due to decisions of the leadership delivery of messages from superiors to subordinates can affect the performance of subordinates if they do not meet the expectations of subordinates. decrease in work motivation of subordinates is very influential on the performance and productivity subordinates. The effect on the disruption of the organization's main goal has been set to profit as much as possible, this is the importance of a communication.Understand the aspects of leadership and human needs is an essential binder for a leader as closely linked with motivation.Keywords:  communication, performance, motivation, media.  ABSTRAK Komunikasi yang terjadi mengikuti alur dari atas ke bawah atau dari bawah ke atas sebagaimana disebut komunikasi vertikal. pemahaman yang ada yaitu komunikasi yang terjadi dari atasan kepada bawahan atau dari bawahan kepada atasan. Isi komunikasi dari atasan kepada bawahan sering berupa pesan yang berisi tugas dan tanggung jawab yang harus dilaksanakan oleh bawahan. demikian juga tentang aturan-aturan yang berlaku dalam menjalankan roda organisasi dalam sebuah lembaga, aturan-aturan yang harus dipatuhi dan dijalankan. Komunikasi ke atas merupakan pesan tentang pekerjaan yang dilakukan oleh bawahan baik secara langsung maupun tidak langsung. demikian juga tentang ketidak puasan akibat keputusan-keputusan pimpinan Penyampaian pesan dari atasan ke bawahan dapat mempengaruhi kinerja dari bawahan bila tidak memenuhi harapan para bawahan. menurunnya motivasi kerja bawahan sangat berpengaruh pada kinerja dan pruduktivitas bawahan. ini berpengaruh pada terganggunya tujuan utama organisasi yang telah ditetapkan untuk meraih keuntungan yang sebesar-besarnya, disinlah letak pentingnya sebuah komunikasi..Kata Kunci: komunikasi, kinerja, motivasi, media.